Interstitial laser photocoagulation of normal lung parenchyma in rats. Issue 8 (1st August 1998) - Fielding, D I; Buonaccorsi, G; Hanby, A; Hetzel, M R; Bown, S G
Abstract : BACKGROUND: Management of peripheral lung tumours may be risky in patients with poor lung function or in the elderly. A new possibility is interstitial laser photocoagulation (ILP) in which tumours are gently coagulated using thin laser fibres placed percutaneously under radiological guidance. This could have a useful palliative role in selected patients, but to be safe the effects on normal lung parenchyma must first be understood. This paper describes the creation and healing of ILP lesions in the normal rat lung. METHODS: ILP was performed using single laser fibres placed percutaneously in the left lung of normal rats under general anaesthetic with radiological guidance (laser power 1–3 W at 805 nm, treatment time 250–1000 s). The lesion size and healing were studied in rats killed at times from three days to six months after treatment, the bursting pressure was measured, and any complications noted. RESULTS: Zones of necrosis up to 12 mm in diameter were produced, the size depending on the laser power and treatment time. Histological examination showed typical thermal effects with complete healing with fibrosis by two months. The effect was very localised with remarkably little effect on the structure and function of the rest of the lung. Adverse effects in the lung parenchyma only occurred if the ILP lesion involved the hilar vessels or the oesophagus, causing pulmonary congestion and perforation, respectively. Pneumothorax was seen in 6% of cases. CONCLUSIONS: ILP with a single fibre can produce a localised zone of necrosis in normal lung parenchyma which heals safely and which has little effect on the rest of the lung. Further study of this technique using multiple fibres in a larger animal model is warranted to see if it is feasible and safe to produce a large enough volume of necrosis to be of value in the treatment of small peripheral lung tumours in patients who are unsuitable for surgery or palliative radiotherapy.